Age at the time of surgery does not compromise the outcome of deepening trochleoplasty: results from under and over 30 years old : knee - Milinkovic, Danko Dan; Zimmermann, Felix; Fluegel, Julian; Schmidt, Sebastian; Balcarek, Peter (Knee surgery, sports traumatology, arthroscopy, 2025)
Purpose This study aimed to evaluate whether age at the time of surgery influences patient-reported outcome measures (PROMs) in patients undergoing tailored surgical treatment for lateral patellar dislocation (LPD), including deepening trochleoplasty (TP). Methods This retrospective cohort study used a prospectively maintained database. The Banff Patella Instability Instrument 2.0 (BPII 2.0) and a numerical analogue scale (0-10) for patellofemoral pain (PFP) and subjective knee joint function were used to assess patients’ disease-specific quality of life before and after surgery. Preoperative cartilage status was evaluated via the semiquantitative Area Measurement and Depth & Underlying Structures (AMADEUS) scoring system. Results Twenty-nine patients (m/f 4/25) were ≥30 years of age (mean: 35.3; range: 30-51) and formed the study group (SG), and 127 patients (m/f 39/88) were <30 years of age (mean: 20.4; range: 11-29) and formed the control group (CG). The evaluation was performed at a mean of 30 ± 13.2 (SG) and 33.1 ± 13.3 months (CG) post-operatively (p = 0.27). The BPII 2.0 increased from 48.7 ± 21.4 to 85.4 ± 10.7 points (p < 0.0001) (SG) and from 44 ± 20.6 to 78.6 ± 18.4 points (p < 0.0001) (CG), without any significant difference between the groups at the final follow-up (p = 0.24). PFP and subjective knee joint function also improved significantly in both groups (p < 0.0001; p < 0.0001), without any significant difference between the groups at the final follow-up (p = 0.08; p = 0.3). In the SG and the CG, 88.2% and 89.7% of patients, respectively, achieved an MCID of 10 points calculated for the BPII 2.0 (p = 0.99), and no correlation was found for ‘age’ or any evaluated post-operative PROM (all p > 0.1). The AMADEUS scores were 80.1 ± 15 points (CG) and 82.1 ± 14.2 points (SG) (p = 0.57), respectively. Conclusion Deepening TP, as part of a tailored surgical treatment plan for recurrent LPD, yielded satisfying results, irrespective of patient age at the time of surgery. Level of Evidence Level III.
Gesehen am 15.09.2025